Unilateral hilar or paratracheal adenopathy in sarcoidosis: a study of 38 cases - Spann, Richard W. (1971)
The diagnosis of pulmonary sarcoidosis should be considered when unilateral hilar enlargement or a paratracheal mass is present. With this diagnosis in mind, a scalene node biopsy or mediastinoscopy may prevent unnecessary thoracotomy. It is believed that the unilateral stage is only an evanescent stage before the development or regression of bilateral hilar lymphadenopathy.